Functions of emojis in WhatsApp interaction among Omanis. (December 2018) - Al Rashdi, Fathiya
Highlights: The paper explores functions of emojis. The data consists of naturally-occurring WhatsApp interaction. In addition to indicating emotion, emojis can be used to serve other communicative functions. These functions are sometimes complex and overlapped. Abstract: This paper examines the functions of emojis as used by Omani men and women friends and relatives in messages exchanged on WhatsApp. The data consists of naturally occurring WhatsApp conversations taken from one male-only and one-female only WhatsApp groups. In order to determine the types of emojis used and the frequencies, I used what Herring (2004) describes as "coding and counting" in her description of computer-mediated discourses analysis. Then, I performed a qualitative analysis of selected extracts using theories and methods of interactional sociolinguistics. In line with studies such as Dresner and Herring (2010), the analysis of select, representative excerpts including various emojis demonstrates that emojis do not only serve as indicators of users' emotions, but also serve many other communicative functions. They can serve as what Gumperz (1982) calls "contextualization cues"; indication of celebration; indication of approval of others' messages; responses to expressions of thanks and compliments; conversational openings and closings; linking devices; and indication of the fulfillment of a requested task. In other words, emojis serve to create alignments between participants, structure interactive exchanges, and indicate message tone.